Growth, leaf gas exchange and mycorrhizal colonization of three medicinal species submitted to different irradiance levels - Barazetti,Viviane Maria (2022)
ABSTRACT: This study o evaluated growth, leaf gas exchange and arbuscular mycorrhizal fungi root colonization in three medicinal plant species under different irradiance intensities. Fridericia chica (Bonpl.) L.G.Lohmann, Mikania laevigata Sch.Bip. ex Baker and Varronia curassavica Jacq. were propagated by cutting and cultivated for 120 days in artificially shaded environments using black shade-type screens, obtaining four irradiance levels: 100%, 70%, 50% and 30%. The experimental design was completely randomized in a 3 x 4 factorial scheme (three plant species and four irradiation levels) with seven replicates. The three medicinal species showed higher liquid assimilation, mass growth and arbuscular mycorrhizal fungi root colonization rates when exposed to environments with 70% light availability. In relation to physiological responses, V. curassavica presented higher photosynthetic rate, stomatal conductance and transpiration when submitted to 70% irradiance, being able to be cultivated in more open environments with higher irradiation levels. Conversely F. chica and M. laevigata presented shade tolerance characteristics. At the initial growth phase, the results obtained can be used as indicators to recommend the ideal cultivation environment for these species in agroforestry systems.